Seed yield of linseed varieties grown as ‘paira’ crop as influenced by dates of sowing (Journal of Applied and Natural Science, 2018)
Linseed is an industrial crop cultivated for its seeds, fibres and oil purpose. Linseed crop can met their requirement i.e. moisture and nutritional demand from stored soil moisture and residual fertility status in "utera? or "paira? system of cropping. On the basis of this fact an experiment was conducted on “Seed yield of linseed varieties grown as paira crop as influenced by dates of sowing” in red and laterite zone of West Bengal during rabi season of 2012-13 and 2013-14 at Rice Research Station, Bankura, West Bengal, India. Poor in organic matter content, available phosphate and bases, hard structure of iron and aluminium patterned as honeycomb are present in the subsurface regions of the profiles and kaolinite is the predominant clay minerals of red and lateritic zone (western part) of West Bengal. This experiment was laid out in a split-plot design with three replications and compared two factors (dates of sowing and linseed varieties). Objective was identifying the optimum date of sowing and suitable linseed varieties grown as „paira? crop under changed climate in red and laterite zone of West Bengal. The experimental results revealed that the highest seed yield (534 kg ha-1 as pooled value) was recorded from the treatment D1 i.e. linseed sown on 15th November. The lowest seed yield (489.2 kg ha-1 as pooled value) was obtained with treatment D3 i.e. linseed sown on 29th November. Among linseed varieties, T-397 has yielded highest seed yield (573.4 kg ha-1 as pooled value). Lowest seed yield (409. 3 kg ha-1 as pooled data) was recorded from Neela variety. From the present study it may be concluded that linseed sown on 15th November is the best time and T-397 is the suitable linseed variety grown as "paira? crop under changed climate in red and laterite zone of West Bengal.